(3JdbjM GdCacGQ aj eYQaI bUQ hWhd Gddjd hGdfgGQs - (3eMeO GdhMjTj Hf YHO Gddg GdJhfSj GdWQGHdSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC GdCadGc GdOGFQI hUhQgG CeG HYO , ajbhd eMeO GdhMjTi Hf YHO Gddg Gfg bO SCdfi HYV GdENhGf Cf CLeY dg ef cJH GdChdjf eNJUQkG ai Yde GdYGe s
(3BNQgG (B:s
(3hgG CfG CUfY dc LOhdkG dJYde efg OhQGf GdOQGQi Ydi GdSGYGJ ai Gddjd hGdfgGQ , hgh gPG ceG JQi s
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs